Bit error probability of the M‐QAM scheme subject to multilevel double gated additive white Gaussian noise and η‐μ, κ‐μ, or α‐μ fading. Issue 12 (15th July 2019) - Silva, Hugerles S.; Queiroz, Wamberto J. L.; Almeida, Danilo B. T.; Madeiro, Francisco; Alencar, Marcelo S.
Abstract: This paper presents new and exact expressions for the bit error probability (BEP) of the square M ‐ary quadrature amplitude modulation scheme subject to η ‐ μ, κ ‐ μ or α ‐ μ fading and multilevel double gated additive white Gaussian noise, which is composed by the sum of a white Gaussian component of variance σ g 2 and a white Gaussian noise component of variance σ i 2 gated by a discrete random process defined in continuous time, which takes values into a finite discrete set. BEP curves, with and without imperfect channel estimation, corroborated by simulations using the Monte Carlo method, are presented for different values of parameters that characterize mathematically the channel. Abstract : This paper presents exact new expressions for the bit error probability (BEP) of the square M ‐ary quadrature amplitude modulation ( M ‐QAM) scheme subject to η‐μ, κ‐μ or α‐μ fading and multilevel double gated additive white Gaussian noise (G 2 AWGN). BEP curves, corroborated by simulations using the Monte Carlo method, for different values of parameters that characterize mathematically the channel are presented.